
要过程,简便计算
(1-2分之1-3分之1-4分之4-5分之1)乘(1+2分之1+3分之1+4分之1+5分之1+6分之1)-(1-2分之1-3分之1-··-6分之1)乘(1+2分之1+··...
(1-2分之1-3分之1-4分之4-5分之1)乘(1+2分之1+3分之1+4分之1+5分之1+6分之1)-(1-2分之1-3分之1-··-6分之1)乘(1+2分之1+··+5分之1)
展开
1个回答
展开全部
原式=(1-1/2-1/3-1/4-1/5)*(1+1/2+1/3+1/4+1/5)+1/6*(1-1/2-1/3-1/4-1/5)-(1-1/2-1/3-1/4-1/5-1/6)*(1+1/2+1/3+1/4+1/5)
=(1+1/2+1/3+1/4+1/5)*【1-1/2-1/3-1/4-1/5-(1-1/2-1/3-1/4-1/5-1/6)】+1/6*(1-1/2-1/3-1/4-1/5)
=1/6*(1+1/2+1/3+1/4+1/5)+1/6*(1-1/2-1/3-1/4-1/5)
=1/6*(1+1/2+1/3+1/4+1/5+1-1/2-1/3-1/4-1/5)
=1/6*2=1/3
=(1+1/2+1/3+1/4+1/5)*【1-1/2-1/3-1/4-1/5-(1-1/2-1/3-1/4-1/5-1/6)】+1/6*(1-1/2-1/3-1/4-1/5)
=1/6*(1+1/2+1/3+1/4+1/5)+1/6*(1-1/2-1/3-1/4-1/5)
=1/6*(1+1/2+1/3+1/4+1/5+1-1/2-1/3-1/4-1/5)
=1/6*2=1/3
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询